Genetic Rescue and the Plight of Ponui Hybrids - Undin, Malin; Lockhart, Peter J.; Hills, Simon F. K.; Castro, Isabel (Frontiers in Conservation Science, 2021)
Long-term sustainable and resilient populations is a key goal of conservation. How to best achieve this is controversial. There are, for instance, polarized views concerning the fitness and conservation value of hybrid populations founded through multi-origin translocations. A classic example concerns Apteryx (kiwi) in New Zealand. The A. mantelli of Ponui Island constitute a hybrid population where the birds are highly successful in their island habitat. A key dilemma for managers is understanding the reason for this success. Are the hybrid birds of Ponui Island of “no future conservation value” as recently asserted, or do they represent an outstanding example of genetic rescue and an important resource for future translocations? There has been a paradigm shift in scientific thinking concerning hybrids, but the ecological significance of admixed genomes remains difficult to assess. This limits what we can currently predict in conservation science. New understanding from genome science challenges the sufficiency of population genetic models to inform decision making and suggests instead that the contrasting outcomes of hybridization, ”outbreeding depression” and ”heterosis”, require understanding additional factors that modulate gene and protein expression and how these factors are influenced by the environment. We discuss these findings and the investigations that might help us to better understand the birds of Ponui, inform conservation management of kiwi and provide insight relevant for the future survival of Apteryx.